Neonatal Adenoviral Myocarditis – A Case Report and Review of Literature - Roy, Amrita; Chowdhury, Labanya; Mukhopadhyay, Debadatta; Das Dutta, Alokananda (Journal of Nepal Paediatric Society, 2021)
Adenoviruses are DNA viruses that typically cause mild self-limited disease mostly involving the respiratory tract, gastrointestinal tract or conjunctiva. Typical respiratory symptoms include fever, pharyngitis, tonsillitis, cough, and sore throat but rare associations with severe disease such as myocarditis have been reported. Current treatment options are limited to usage of intravenous immunoglobulins (IVIGs) or antiviral agent Cidofovir, however usage of the latter is limited due to reports on drug induced adverse reactions. In this case report we describe an infant with severe myocarditis in whom Adenovirus was revealed to be the identifiable cause. The infant was treated with IVIG which is believed to act as an immunomodulatory agent. The infant recovered completely. Our conclusion is that patients with myocarditis caused by adenovirus are likely to benefit from early treatment with IVIGs.